Science – Policy Interactions in Climate Change Mitigation and Adaptation to Climate Change: Lessons from Latin America - Daza Aragón, Paola; Le Coq, Jean-François (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Science–policy interactions are exchanges among key stakeholders looking to reconcile value systems and interests to ultimately, influence decision-making processes through knowledge exchange and generation. These interactions are the way in which climate science tries to reach policy to create feasible solutions, with properly addressed objectives and processes for implementation and evaluation. Knowledge uptake highly depends on adjusting scientific language and information to stakeholder capability and interests, and on communicating concrete inputs or recommendations for decision making. Science–policy interfaces legitimize collaborations between science and policy, by delimitating and coordinating stakeholder roles and enabling their participation in knowledge generation and problem-solving processes.